Glycosyl-Phosphatidyl-Inositol (GPI)-Anchors and Metalloproteases: Their Roles in the Regulation of Exosome Composition and NKG2D-Mediated Immune Recognition - López-Cobo, Sheila; Campos-Silva, Carmen; Valés-Gómez, Mar (Frontiers in Cell and Developmental Biology, 2016)
Communication within the immune system depends on the release of factors that can travel and transmit information at points distant from the cell that produced them. In general, immune cells use two key strategies that can occur either at the plasma membrane or in intracellular compartments to produce such factors, vesicle release and proteolytic cleavage. Release of soluble factors in exosomes, a subset of vesicles that originate from intracellular compartments, depends generally on biochemical and lipid environment features. This physical environment allows proteins to be recruited to membrane microdomains that will be later endocytosed and further released to the extracellular milieu. Cholesterol and sphingolipid rich domains (also known as lipid rafts or detergent-resistant membranes, DRMs) often contribute to exosomes and these regions are rich in proteins modified with Glycosyl-Phosphatidyl-Inositol (GPI) and lipids. For this reason, many palmitoylated and GPI-anchored proteins are preferentially recruited to exosomes. In this review, we analyse the biochemical features involved in the release of NKG2D-ligands as an example of functionally related gene families encoding both transmembrane and GPI-anchored proteins that can be released either by proteolysis or in exosomes, and modulate the intensity of the immune response. The immune receptor NKG2D is present in all human Natural Killer and T cells and plays an important role in the first barrier of defence against tumor and infection. However, tumor cells can evade the immune system by releasing NKG2D-ligands to induce down-regulation of the receptor. Some NKG2D-ligands can be recruited to exosomes and potently modulate receptor expression and immune function, while other are more susceptible to metalloprotease cleavage and are shed as soluble molecules. Strikingly, metalloprotease inhibition is sufficient to drive the accumulation in exosomes of ligands otherwise released by metalloprotease cleavage. In consequence, NKG2D-ligands appear as different entities in different cells, depending on cellular metabolism and biochemical structure, which mediate different intensities of immune modulation. We discuss whether similar mechanisms, depending on an interplay between metalloprotease cleavage and exosome release, could be a more general feature regulating the composition of exosomes released from human cells.